Insecticide Susceptibility and Resistance Development in Malathion Selected Aedes albopictus (Skuse) - Selvi, S.; Edah, M.A.; Nazni, W.A.; Lee, H.L.; Tyagi, B.K.; Sofian-Azirun, Mohd; Azahari, A.H. (Malaysian Society of Parasitology and Tropical Medicine, 2010)
Aedes albopictus was bioassayed to determine resistance development to malathion (OP). Two methods were applied, including WHO larval bioassay to determine the susceptibility to lethal concentration (LC), and adult bioassay to determine lethal time (LT). Larvae from colonies that had undergone selection pressure with malathion to yield 50 mortality were further subjected to selection for subsequent 10 generations. Selection of Ae. albopictus with malathion could relatively induce a consistent resistance ratio of 1.0 throughout 10 generations. It was noted that Ae. albopictus larvae showed less susceptibility to malathion compared to adults. The susceptibility test of adult mosquitoes to diagnostic dosage of 5.0 malathion-impregnated paper showed a variety of susceptibility to malathion when compared to the susceptible strain. Bioassay results indicated that the LT 50 values of malathion-selected Ae. albopictus ranged between 11.5 - 58.8 minutes for ten consecutive generations. Biochemical enzyme studies indicated that there was a significant difference (p < 0.05) in esterase level in malathion-selected mosquitoes compared to non-selected control. Electrophoretic patterns of non-specific esterases at different life stages in malathion-selected Ae. albopictus suggested that non-specific esterases do not play a role in resistance of malathion-selected Ae. albopictus.